Prophetic Pedagogy in Practice: A Holistic Teaching Model for Enhancing Learning in Indian Primary Schools: Prophetic Pedagogy for Effective Teaching and Learning - K. Sayyid Mubashir; Muhammed Swadique PC (Primary Education Insight, 2026)
This study examines the pedagogical methods of Prophet Muhammad ﷺ as a comprehensive educational model and explores their relevance in contemporary primary education in India. Using a qualitative library research design, data were collected from major hadith sources, including Sahih al-Bukhari, Sahih Muslim, Sunan Abu Dawud, Sunan at-Tirmidhi, and Sunan Ibn Majah, as well as supporting literature on modern educational theory. The analysis employed content analysis to identify key teaching principles and categorize them into coherent pedagogical frameworks. The findings reveal that Prophetic pedagogy is characterized by an integration of exemplary conduct, affective engagement, dialogic learning, multimodal instructional strategies, and adaptive teaching. The Prophet ﷺ employed methods such as dialogue, analogy, repetition, visualization, and contextual guidance to address diverse learners effectively. These approaches align closely with contemporary theories, including constructivism, social-emotional learning, and differentiated instruction. In the context of primary education, these methods are particularly effective in fostering student engagement, enhancing comprehension, and supporting character development. The study highlights the relevance of Prophetic pedagogy in addressing current challenges in elementary education, especially in diverse and complex classroom settings. It contributes theoretically by bridging classical Islamic pedagogical concepts with modern educational frameworks. Practically, it offers insights for teachers to design more holistic and learner-centered instructional practices. However, the study is limited by its reliance on textual analysis and the absence of empirical validation. Future research is recommended to implement and evaluate these pedagogical principles in real classroom environments.